Genome-wide analysis of lipolytic enzymes and characterization of a high-tolerant carboxylesterase from Sorangium cellulosum - Yuan, Shu-Fei; Yue, Xin-Jing; Hu, Wei-Feng; Wang, Ye; Li, Yue-Zhong (Frontiers in Microbiology, 2023)
Microorganisms are important sources of lipolytic enzymes with characteristics for wide promising usages in the specific industrial biotechnology. The cellulolytic myxobacterium Sorangium cellulosum is rich of lipolytic enzymes in the genome, but little has been investigated.Here, we discerned 406 potential lipolytic enzymes in 13 sequenced S. cellulosum genomes. These lipolytic enzymes belonged to 12 families, and most are novel with low identities (14%-37%) to those reported. We characterized a new carboxylesterase, LipB, from the alkaline-adaptive So0157-2. This enzyme, belonging to family VIII, hydrolyzed glyceryl tributyrate and p-nitrophenyl esters with short chain fatty acids (≤C12), and exhibited the highest activity against p-nitrophenyl butyrate. It retained over 50% of the activities in a broad temperature range (from 20°C to 60°C), alkaline conditions (pH 8.0-9.5), and the enzymatic activity was stable with methanol, ethanol and isopropanol, and stimulated significantly in the presence of 5 mM Ni 2+ . LipB also exhibited βlactamase activity on nitrocefin, but not ampicillin, cefotaxime and imipenem. The bioinformatic analysis and specific enzymatic characteristics indicate that S. cellulosum is a promising resource to explore lipolytic enzymes for industrial adaptations.